Implementasi Perda Ketertiban Umum di Pohuwato: Antara Represi dan Rehabilitasi Sosial dalam Penanggulangan Prostitusi - Cendris Humu; Zamroni Abdussamad; Supriyadi A. Arief (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study analyzes the implementation of Pohuwato Regency Regional Regulation Number 4 of 2020 concerning the Implementation of Public Order and Community Peace in addressing prostitution, focusing on the disparity between repressive and rehabilitative approaches; the background of the research is based on the gap between normative provisions and implementation reality, characterized by an increase in raids without a corresponding decline in prostitution practices. The research aims to examine the normative position of the regional regulation within the legal hierarchy and to evaluate the effectiveness of law enforcement in the field; the method employed is empirical legal research (socio-legal research) through in-depth interviews, observation, and secondary data analysis. The findings reveal that, normatively, the regional regulation potentially conflicts with the hierarchy of laws and regulations due to the imposition of detention sanctions without judicial oversight mechanisms, while implementation-wise, law enforcement only targets sex workers through a repressive approach without adequate social rehabilitation and economic empowerment programs. The implications of this study underscore the necessity of revising the regional regulation to align with the supremacy of law and integrating a rehabilitative approach into a more comprehensive and equitable prostitution prevention policy.